The dinosaurs of Waterhouse Hawkins : an illuminating history of Mr. Waterhouse Hawkins, artist and lecturer - Kerley, Barbara (Scholastic, 2001)
The true story of Victorian artist Benjamin Waterhouse Hawkins, who built life-sized models of dinosaurs in the hope of educating the world about what these awe-inspiring ancient animals and what they were like.